Comorbidities and HCV coinfection in the management of HIV+ patients: Evidence from the Italian clinical practice - Elisabetta Garagiola; Emanuela Foglia; Lucrezia Ferrario; Paola Meraviglia; Alessandro Tebini; Barbara Menzaghi; Chiara Atzori; Giuliano Rizzardini; Teresa Bini; Antonella D'Arminio Monforte; Davide Croce (Health Economics Review, 2020)
Background: Since HIV+ treatment has become more effective, the average age of people living with HIV (PLWHIV) has increased, and consequently the incidence of developing comorbidities, making the clinical and economic management of HIV+ patients more complex. Limited literature exists regarding the management of comorbidities costs. This study is aimed at defining and comparing the total annual costs of comorbidities, in an Italian cohort of HIV and HIV/HCV patients, from the National Healthcare Service perspective. The authors hypothesised that there are higher costs, for patients with multiple comorbidities, and a greater consumption of resources for HIV/HCV coinfected patients versus HIV mono-infected patients. Methods: An observational retrospective multi-centre health-economics study, enrolling HIV+ and HIV/HCV consecutive patients with at least one comorbidity, was conducted. The consecutive cases, provided by three Italian infectious diseases centres, were related to the year 2016. The enrolled patients were on a stable antiviral therapy for at least six months. Demographic and clinical information was recorded. Costs related to HIV and HCV therapies, other treatments, medical examinations, hospitalizations and outpatient visits were evaluated. Data from monoinfected and co-infected groups of patients were compared, and the statistical analysis was performed by t-tests, chi-square and ANOVA. A sub-analysis excluding HCV therapy costs, was also conducted. The hierarchical sequential linear regression model was used to explore the determinants of costs, considering the investigated comorbidities. All analyses were conducted with a significant level of 0.05. Results: A total of 676 patients, 82% male, mean age 52, were identified and divided into groups (338 monoinfected HIV+ and 338 co-infected HIV/HCV patients), comparable in terms of age, gender, and demographic characteristics. A trend towards higher annual costs, for patients with multiple comorbidities was observed in HIV mono-infected patients (respectively exteuro 8272.18 for patients without comorbidities and exteuro 12,532.49 for patients with three or more comorbidities, p-value: 0.001). Excluding anti-HCV therapies costs, HIV/HCV co-infected patients generally required more resources, with statistically significant differences related to cardiovascular events ( exteuro10, 116.58 vs exteuro11,004.28, p-value: 0.001), and neurocognitive impairments events ( exteuro7706.43 vs exteuro11,641.29 p- value: < 0.001). Conclusions: This study provides a differentiated and comprehensive analysis of the healthcare resources needed by HIV and HIV/HCV patients with comorbidities and may contribute to the decision process of resources allocation, in the clinical management of different HIV+ patient populations.
Keywords: 330; HIV +; HIV/HCV; Comorbidities; Management; Economic evaluation